2021
DOI: 10.1021/acs.jproteome.0c00806
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Effect of Passage Number on HT29 Cell Line Based on the Cell Metabolomic Approach

Abstract: The passage number is an important factor when designing the cell line-based experiment. Although HT29 cells were widely used in the laboratory for colorectal cancer studies, the impact of cell passage number on the HT29 cells was still unknown. In this study, phenotypic assay and metabolomic approach were applied to analyze the systemic effects of passage numbers (passage 4, 10, and 16) on the HT29 cells. The results showed that the increased cell passage number affected the cell cycle distribution and also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This was in agreement with the study reported by Welch, Neri and Nicolson ( 21 ), whereby it was stated that the metastatic potential of each tumour cell clone drifts with passage number. In 2021, a study by Cao et al ( 22 ) highlighted the influence of increased cell passage number on the proliferation and migration capacity of HT29 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This was in agreement with the study reported by Welch, Neri and Nicolson ( 21 ), whereby it was stated that the metastatic potential of each tumour cell clone drifts with passage number. In 2021, a study by Cao et al ( 22 ) highlighted the influence of increased cell passage number on the proliferation and migration capacity of HT29 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al (2021) conducted a study using HT29 colorectal cancer cells, revealing a negative correlation between HT29 proliferation and an increasing PN. As the PN increased, there was an observed rise in the population of HT29 cells in the G0/G1 phase, while the cell population in the S and G2 + M phases decreased.…”
Section: Phenotypic and Genotypic Variability In Cell Linesmentioning
confidence: 99%
“…hES were even affected by different passaging methods, such as enzymatic versus nonenzymatic dissociation of cell clusters, the latter of which appeared to induce chromosomal aberrations [11]. Increased passage numbers of HT29 cells were reported to induce a decrease in cell proliferation and their ability to migrate, and led to altered cell cycle distributions [12]. Hence, putative differences in passage numbers that are probably cell-line-specific have to be excluded before starting new experiments.…”
Section: Original Papermentioning
confidence: 99%